Can community-based health insurance nudge preventive health behaviours? Evidence from rural Uganda - Emmanuel Nshakira-Rukundo; Essa Chanie Mussa; Nathan Nshakira; Nicolas Gerber; Joachim von Braun (University of Bonn, Center for Development Research (ZEF), 2019)
Community-based health insurance (CBHI) schemes have emerged as strong pathways to universal health coverage in developing countries. Their examination has largely focussed on their impacts on financial protection and on the utilisation of curative health services. However, very little is known about their possible effect on utilisation of preventive health services and strategies and yet developing countries continue to carry a burden of easily preventable illnesses. To understand if this effect exists, we carry out a cross-sectional survey in communities served by a large CBHI scheme in rural south-western Uganda. We then apply inverse probability weighting of the propensity score to analyse quasiexperimental associations. We find that the probabilities for using long-lasting mosquito nets, vitamin A and iron supplementation and child deworming were significantly increased with participation in CBHI. We postulate that this effect is partly due to information diffusion and social learning within CBHI-participating burial groups. This work gives insight into the broader effects of CBHI in developing countries, beyond financial protection and utilisation of hospital-based services.
Keywords: I13; I15; I10; 330; Community-based health insurance; Preventive Health; Inverse Probability Weighting; Rural Uganda